TELEREHABILITATION FOR DEMENTIA PATIENTS DURING PANDEMIC CORONAVIRUS DISEASE (COVID-19): A LITERATURE REVIEW - Salsabilah, Andi; Krismondani, Ratna Dwi; Aulia, Rizka Dwi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: Dementia is a chronic and progressive intellectual function syndrome in the elderly. According to WHO, the prevalence of dementia in the world in 2018 reached 50 million people and is estimated to reach 152 million in 2050. Rehabilitation is an effort to minimize disturbances in the life quality of dementia patients. However, The COVID-19 pandemic has emerged as a new obstacle in providing rehabilitation services for dementia patients. Telerehabilitation is very useful in helping rehabilitate dementia patients in the era of the COVID-19 pandemic.Purpose: The technology use of telerehabilitation in geriatrics dementia is potentially improving medical access to deliver rehabilitation therapy of pandemic COVID-19.Method: This study was conducted by literature review from Science Direct, PubMed, and The American Journal of Geriatric Psychiatry library database, with search terms: "Telemedicine," "Telerehabilitation," "Dementia," "Geriatric" by Boolean search operators. There are 226 records identified and screened by title and abstract. Their studies are finally fulfilled our criteria and will be reviewed.Result: We examined three studies and presented qualitative and quantitative scores for two telerehabilitation methods. Two methods are commonly used for video conference and virtual reality. Video conferences are still the most capable method for dementia telerehabilitation.Conclusion: The technology use of telerehabilitation in geriatrics dementia is potentially improving medical access to deliver rehabilitation therapy to patients and caregivers at a distance during this pandemic.